Assessing Student Satisfaction and Improving Efficiency: A Study on University Cafeteria. - Rahman, Ashiqur (American Journal of Health Education)
The university cafeteria is a crucial element in shaping students' dining experiences and their physical well-being. This study was conducted at a public university in Bangladesh. This research has a dual purpose: firstly, to assess student satisfaction with the university cafeteria using key indicators and secondly, to identify critical factors influencing this satisfaction through advanced data analysis employing recursive feature elimination (RFE). The ultimate goal is to enhance cafeteria services, align them with student preferences, and boost overall satisfaction. Data collection involved 150 paper-based questionnaires with mixed data types, including questions based on prior research assessments. The model-building process included the chi-squared test and the recursive feature elimination process. The study identifies 12 factors significantly affecting cafeteria food satisfaction, with four factors having a notable impact: meal type and freshness, staff attitude, and wait length. This research highlights the interconnectedness of seemingly distinct cafeteria factors and their potential to influence health outcomes. Practical recommendations are made for improving cafeteria efficiency and adapting to changing student needs. Health education interventions aimed at enhancing the cafeteria experience for university students should include a quantitative analysis of factors impacting students' overall cafeteria satisfaction.